The Analyses of Albanian Budget Expenditure - Nano, Dorjana; Guga, Eduina (European Journal of Economics and Business Studies, 2015)
Public expenditure efficiency has been an issue of concern for many researchers. Studies have shown that public budget of the developed and developing economies is not optimally allocated and managed. Anyway, discrepancies are found between both economies. This paper aims to investigate and critical analyze the allocation of public expenditure in the Republic of Albania. In addition, it provides some relevant comparison of the performance indicators among Albania, regional countries and OECD states. Data provided by the Ministry of Finance and Open Access Data are evaluated by considering the functional classification of the budget expenditure. Results of this study suggest that Albania spends more on social protection and social security, and less on education and health compared with the average of the EU countries and OECD countries. In addition, inefficiency of the public sector is discovered. This research recommends the necessity in the improvement of input allocation by using 70 percent less resources to achieve the same amount of public output and consequently contributing positively on fiscal consolidation.